2009
DOI: 10.1098/rsbl.2009.0864
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity in an awake chimpanzee in response to the sound of her own name

Abstract: The brain activity of a fully awake chimpanzee being presented with her name was investigated. Event-related potentials (ERPs) were measured for each of the following auditory stimuli: the vocal sound of the subject's own name (SON), the vocal sound of a familiar name of another group member, the vocal sound of an unfamiliar name and a non-vocal sound. Some differences in ERP waveforms were detected between kinds of stimuli at latencies at which P3 and Nc components are typically observed in humans. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…Our findings showed that the chimpanzee elicited a neural activity pattern indicating automatic detection of change in auditory stimuli, similar to a well-known pattern in humans known as ‘mismatch negativity’ [28]. Moreover, selective neural responses to the vocal sound of the subject's own name were observed, in comparison to vocalization of other individuals' names [29]. These findings demonstrate the usefulness of the sedation-free ERP measurement in investigating the neural basis of cognitive dynamics in the chimpanzee brain.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings showed that the chimpanzee elicited a neural activity pattern indicating automatic detection of change in auditory stimuli, similar to a well-known pattern in humans known as ‘mismatch negativity’ [28]. Moreover, selective neural responses to the vocal sound of the subject's own name were observed, in comparison to vocalization of other individuals' names [29]. These findings demonstrate the usefulness of the sedation-free ERP measurement in investigating the neural basis of cognitive dynamics in the chimpanzee brain.…”
Section: Introductionsupporting
confidence: 83%
“…We previously reported an examination of her ERPs in response to auditory stimulation [28], [29]. Our findings showed that the chimpanzee elicited a neural activity pattern indicating automatic detection of change in auditory stimuli, similar to a well-known pattern in humans known as ‘mismatch negativity’ [28].…”
Section: Introductionsupporting
confidence: 73%
“…Since her arrival at the Great Ape Research Institute when she was 2 years and 1 month old, she has spent her time with other chimpanzees. At the time of the present experiments, Mizuki was 11 years old and had undergone other behavioral cognitive experiments2425, as well as earlier ERP experiments15161726. This research was conducted in accordance with the Guide for the Care and Use of Laboratory Animals of Hayashibara Biochemical Laboratories, Inc., and the Weatherall report, The use of non-human primates in research .…”
Section: Methodsmentioning
confidence: 99%
“…After a long period of step-by-step training, we succeeded in measuring EEG in a fully-awake adult chimpanzee for the first time151617. In the present experiment, we measured ERPs in response to pictures which were a subset of the stimuli used in the chimpanzee memory experiment, in which enhanced memory for affective over neutral pictures was found12.…”
mentioning
confidence: 97%
“…Staying still for a long period of time without sleeping is rather challenging for many species, thus the training times needed for animal brain research are usually arduous and commonly, only one or two animals are trained for the task. In a recent experiment, scalp-EEG was measured from one chimpanzee, for whom the training took 0.5 years and the recording 50 days [33]; this one individual already trained for the task was also the subject for the subsequent experiments [39], [40]. In intracranial EEG experiments of macaque monkeys, the animal training time is often not mentioned, or noted simply requiring “lengthy” training (e.g., [41][43]).…”
Section: Discussionmentioning
confidence: 99%